Tradisi Kasohaka pada Masyarakat Kadatua dalam Upaya Mitigasi Bencana Alam - Ramayanti Romalita; Mega Mustikasari; Muh. Suismawansyah; Ridwan Ridwan (Journal on Education, 2023)
This research is a qualitative descriptive study, from which data were obtained through observation and interviews with the Kadatua community. The purpose of this study is to examine the meaning and values of the kasohaka tradition in the Kadatua community, so that it becomes a reference for the Kadatua community, especially in the application of traditional values that exist in the community. The research was conducted through several stages, namely: Observation, Interview, Documentation, Data Analysis. The kasohaka tradition is carried out by means of residents preparing "kantila" (fill gutters) which will be placed on the kasohaka building. Baruga was made as a building for the implementation of the kasohaka ritual, in this baruga the community led by the traditional leader to offer prayers to avoid disaster. Kasohaka tradition contains values such as religious values, mutual cooperation values, cultural values and the value of deliberation. According to people's beliefs if this tradition is not carried out there will be strong winds, heavy rain and big waves, the kasohaka tradition can mitigate disasters because they believe in the prayers they say to the creator to exorcise "demons". disaster bearer.